Versatile Synthesis of Multivalent Porphyrin–Peptide Conjugates by Direct Porphyrin Construction on Resin. Issue 34 (11th July 2022) - Wu, Yue; Chau, Ho‐Fai; Yeung, Yik‐Hoi; Thor, Waygen; Kai, Hei‐Yui; Chan, Wai‐Lun; Wong, Ka‐Leung
Abstract: Multifunctional porphyrin–peptide conjugates with different propensities for self‐assembly into various supramolecular nanoarchitectures play important roles in advanced materials and biomedical research. However, preparing prefunctionalized core porphyrins by traditional low‐yielding statistical synthesis and purifying them after peptide ligation through many rounds of HPLC purification is tedious and unsustainable. Herein, we report a novel integrated solid‐phase synthetic protocol for the construction of porphyrin moieties from simple aldehydes and dipyrromethanes on resin‐bound peptides directly to form mono‐, cis / trans ‐di‐, and trivalent porphyrin–peptide conjugates in a highly efficient and controllable manner; moreover, only single final‐stage HPLC purification of the products is needed. This efficient strategy enables the rapid, greener, and substrate‐controlled diversity‐oriented synthesis of multivalent porphyrin–(long) peptide conjugate libraries for multifarious biological and materials applications. Abstract : A practical integrated solid‐phase synthetic protocol is reported for the direct construction of porphyrin moieties on resin‐bound peptides from simple aldehyde and dipyrromethane building blocks. Monovalent, cis / trans ‐divalent, and trivalent porphyrin–(long) peptide conjugate products can be formed by this method in a highly efficient and controllable manner.